DORNASE ALFA IN RUSSIA: 15 YEARS LATER. EFFICACY OF THE DRUG IN THE BASIC TREATMENT IN CHILDREN WITH CYSTIC FIBROSIS - O. I. Simonova; O. F. Lukina ("Paediatrician" Publishers LLC, 2012)
The 15-years practice of Pulmozyme (dornase alfa) usage showed its high efficacy and safety in cystic fibrosis treatment in children of various age, including infants. The efficacy of the drug is associate with clinical effects: strong mucolytic, anti-inflammatory and antibacterial effects. The appropriateness of including this into the complex of the basic therapy of cystic fibrosis in order to prevent and treat chronic bronchitis and chronic polypous pansinusitis as soon as the disease is diagnosed was confirmed in studies. Regular use of this drug results in relapse rate decrease, remission periods prolongation and maintenance of external respiration at stable level, which enable patients to live active life. The therapeutic effect of dornase alfa depends on strict compliance to directions of its usage, as this agent is a proteolytic enzyme.